Association of Smoking and Alcohol with Acute Pancreatitis in Patients presenting in Tertiary Care Hospital Lahore - Rabia Ramzan, Aqeel Ashraf, Muhammad Hassaan, Abeera Ishaq Butt, Syed Asghar Naqi, Fowad Karim, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Acute pancreatitis refers to the reversible inflammatory process of pancreas. Various researches report that smoking and heavy alcohol consumption increase the risk of acute pancreatitis. Material and methods: This research, carried out at Department of Surgery in Mayo Hospital, Lahore, has a sample size of 294, sampling technique being non probability sampling. Inclusion and exclusion criteria were applied. Results: Alcoholism and smoking were found to be the risk factors for acute pancreatitis among people participating in this study. Discussion: Both smoking and alcoholism are risk factors for acute pancreatitis, this is supported by various researches done in the past. Strength of this study includes a large sample size as well as inclusion of both cases and controls. However, effect of smoking and alcoholism on outcome of these patients has not been studied in this research. Conclusion: Public health measures for awareness and timely management of the diagnosed cases can reduce the disease burden and disease severity.